2009
DOI: 10.1111/j.1399-3038.2008.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of once‐daily fluticasone furoate nasal spray in children with seasonal allergic rhinitis treated for 2 wk

Abstract: The objective of this study was to evaluate the efficacy and safety of fluticasone furoate (FF) nasal spray 55 and 110 microg once daily in children with seasonal allergic rhinitis (SAR). Patients (n = 554) received placebo nasal spray or FF, administered using a unique side-actuated device, in a 2-wk, randomized, double-blind study. Symptoms were evaluated by patients using a 4-point categorical scale. Efficacy assessments included reflective and instantaneous total nasal symptom scores (r/iTNSS). Primary ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 16 publications
4
25
1
Order By: Relevance
“…The only adverse events that were reported in at least 3% of patients in either group and were more common with FFNS than placebo were epistaxis (15 and 8%, respectively) and nasopharyngitis (5 and 1%, respectively). These results corroborate previous findings in perennial and seasonal allergic rhinitis [16][17][18][19][20][21][22][23][24][25] and are consistent with the low absolute bioavailability (Ͻ0.5%) of fluticasone furoate. 15 FFNS was also well tolerated in a randomized, double-blind, placebo-controlled study involving 12 months of daily treatment of perennial allergic rhinitis.…”
Section: Discussionsupporting
confidence: 94%
“…The only adverse events that were reported in at least 3% of patients in either group and were more common with FFNS than placebo were epistaxis (15 and 8%, respectively) and nasopharyngitis (5 and 1%, respectively). These results corroborate previous findings in perennial and seasonal allergic rhinitis [16][17][18][19][20][21][22][23][24][25] and are consistent with the low absolute bioavailability (Ͻ0.5%) of fluticasone furoate. 15 FFNS was also well tolerated in a randomized, double-blind, placebo-controlled study involving 12 months of daily treatment of perennial allergic rhinitis.…”
Section: Discussionsupporting
confidence: 94%
“…The percentage of patients with quantifiable plasma levels of FF in the 2e5 years group was low and comparable to that in the 6e14 years group, indicating low systemic exposure both in older and younger children as young as 2 years. The absence of quantifiable plasma levels of FF in most children after 2 or 12 weeks of FFNS 55 and 110 mg was reported in a clinical study in non-Japanese children, 15,16 which is consistent with the results in this study. In adult nonJapanese healthy male and female volunteers, bioavailability of FFNS was assessed as low, 0.5%.…”
Section: Discussionsupporting
confidence: 94%
“…In clinical studies in non-Japanese children aged 2 to <12 years, FFNS 55 and 110 mg had similar AE profiles to the placebo. 15,16 In these studies FFNS 55 and 110 mg were reported to be well tolerated, which is consistent with the results in this study. The absence of quantifiable plasma levels of FF in most patients 0.5e2 h after the last dose in the 12-week treatment period demonstrates low systemic exposure of FFNS 55 mg.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Symptomatic relief of allergic rhinitis begins 8 hours after administration and lasts for 24 hours (Máspero et al, 2008;Nathan RA et al, 2008;Vasar et al, 2008;Baroody et al, 2009;Meltzer et al, 2009). …”
Section: Fluticasone Furoatementioning
confidence: 99%